Volatility Spillovers from US to Emerging Seven Stock Markets: Pre & Post Analysis of GFC - Badshah, Waqar (International Journal of Contemporary Economics and Administrative Sciences, 2021)
This study is conducted to check volatility spillovers from US to Emerging seven stock markets before and after the Global Financial Crisis through the VAR-GARCH model. The pre GFC sub sample data ranges from January 8, 2002 to June 29, 2007 and Post GFC data starts from July 4, 2009 to December 28, 2014. The outcomes of the VAR-GARCH model show that there are significant volatility spillovers from US stock market to emerging seven stock markets in most cases. The correlations reveal that the US stock market is strongly correlated with the Brazilian stock exchange, Mexican stock exchange and Russian stock exchange. These findings suggest that the investors may consider geographical proximity into consideration. The empirical results also mention that the Chinese stock market, Indonesian stock market and Indian stock market have less effect by the volatility spillovers from US stock market. The findings also demonstrate that Brazilian, Mexican and Russian stock markets observed rapid increase in the CCC with the US market.